Answer:
[tex]x^2 + y^2 = 52[/tex]
Step-by-step explanation:
Distance between two points:
Suppose that we have two points, [tex](x_1,y_1)[/tex] and [tex](x_2,y_2)[/tex]. The distance between them is given by:
[tex]D = \sqrt{(x_2-x_1)^2+(y_2-y_1)^2}[/tex]
Equation of a circle:
The equation of a circle with center [tex](x_0,y_0)[/tex] and radius r has the following format:
[tex](x - x_0)^2 + (y - y_0)^2 = r^2[/tex]
Center at the origin;
This means that [tex]x_0 = 0, y_0 = 0[/tex]
So
[tex](x - x_0)^2 + (y - y_0)^2 = r^2[/tex]
[tex](x - 0)^2 + (y - 0)^2 = r^2[/tex]
[tex]x^2 + y^2 = r^2[/tex]
Passes through (4, 6)
The radius is the distance from this point to the center. So
[tex]r = \sqrt{(x_2-x_1)^2+(y_2-y_1)^2}[/tex]
[tex]r = \sqrt{(4-0)^2+(6-0)^2}[/tex]
[tex]r = \sqrt{16+36}[/tex]
[tex]r = \sqrt{52}[/tex]
So
[tex]r^2 = 52[/tex]
Then
[tex]x^2 + y^2 = r^2[/tex]
[tex]x^2 + y^2 = 52[/tex]